s Sinergi Partisipasi Masyarakat Marginal dalam Mewujudkan Kemandirian Desa: Studi Kasus Desa Masgo, Kabupaten Kerinci - Tania, Jira; Azwar, Welhendri; Jamil, Muhamad (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2025)
Masgo Village is one of the remote villages in Kerinci Regency that experiences marginalization in social, economic, and infrastructural aspects. This study aims to examine the extent to which the participation of marginalized communities can synergize with village government efforts in building sustainable village self-reliance. The research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings indicate that despite their marginalized condition, the people of Masgo Village possess strong social capital, such as a spirit of mutual cooperation and high community solidarity. Community participation is evident in various local initiatives, such as road repairs, water resource management, and the formation of farmer groups. However, participation in formal forums like village deliberations remains procedural and lacks inclusivity. The study recommends the need for empowerment strategies and facilitation from the village government so that the community's participatory potential can evolve into a transformative force for achieving village self-reliance.